Exposure to violence and bullying among adolescents in school in Huánuco, Peru - Ayala-Albites, Flor M. (2025)
The purpose of this study was to analyze the relationship between exposure to violence and bullying in adolescents of both sexes, aged 12 to 17, attending a flagship public school in Huánuco. The research was observational and cross-sectional, with a correlational design. The sample was non-probabilistic for convenience and consisted of 126 students. Two instruments were used to collect data: the Violence Exposure Questionnaire and the AVE Test (Harassment and School Violence). The general hypothesis was tested: there is a significant relationship between exposure to school violence and bullying in adolescents, a result obtained using Spearman's rho statistic. The correlation coefficient obtained was 0.877 with a bilateral significance of 0.000, indicating a very strong and significant positive correlation between both variables. A significant correlation was also found with the "home" (0.793) and "street" (0.836) dimensions. This finding highlights that violent environments, especially at home and on the streets, directly impact the increase in bullying, which is an important determining factor in the intensity of bullying experienced by students.